Trójumanna saga. A case of translatio and translation of the Latin culture in Icleand - Bedogni, Beatrice, 1994- (2019)
This work provides a precise analysis of the Trójumanna saga, which is explored concerning acculturation's phenomenon between the Latin culture and the Icelandic literature. This saga has been chosen because it derives from previous sources, that is the Daretis Phrygii De Excidio Troiae Historia. The Icelandic text is compared with the Latin sources, which are the texts of Dares Phrygius, Virgil, Ovid and the Ilias Latina. The essay analyses the influence of the Latin world on the Icelandic culture and it will try to demonstrate how these two different universes collaborate and create a new culture, and this is possible to notice in the process of translation and in these texts, which present the trojan theme. The discussion will focus on the phenomenon of the texts' translation: its role, the changes and the elaborations of the translated texts. Furthermore, the story of the trojan theme during the century and the theme of the idea of translatio imperii et studii hold an essential role in this discussion, because they are strictly linked and they are found in many other medieval cultures, not only in Iceland. Also, the process of acculturation and the Christianization of Iceland will be analysed in detail, because the Church was the vehicle which had transmitted the Latin culture on the island.